Effect of Sodium Boron Hydride (NaBH4) on Waste Polyethylene Terephthalate Pyrolysis - Olam, Mikail; Karaca, Huseyin (Institute of Physics Publishing, 2019)
Polyethylene terephthalate, which is used in many applications today, is very important in terms of nature and source in order to ensure recycling by appropriate methods after use. Because polyethylene terephthalate is a durable and long-lasting thermoplastic which is resistant to many environmental influences. Recovering residual plastics has become mandatory. In this study, the conversion of waste plastic to a new liquid fuel by polyethylene terephthalate (PET) pyrolysis method was investigated. Sodium boron hydride (NaBH4) was used as both catalyst and hydrogen donor in the pyrolysis experiments. Pyrolysis experiments were carried out in a batch reactor under catalytic and non-catalytic conditions, reaction time of 15-90 minutes, reaction temperature of 325-425 °C, solid/solvent ratio of 1/4 and initial nitrogen gas pressure of 20 bar. According to the results obtained, the most suitable reaction temperature was found to be 375-425 °C and the reaction time was 30 minutes. At the reaction times of 30 minutes, the maximum total conversion in non-catalytic conditions of waste polyethylene terephthalate samples was 53.1% at 400 °C reaction temperature and the highest oil + gas yield was 43.7% at 425 °C reaction temperature. In the pyrolysis of polyethylene terephthalate samples in the presence of sodium boron hydride, the maximum total conversion was 55.3% at 400 °C reaction temperature and the highest oil + gas yield was 44.6% at 425 °C reaction temperature. As a result, it can be argued that sodium boron hydride used in pyrolysis experiments of waste polyethylene terephthalate acts as both catalytic and hydrogen donor. © Published under licence by IOP Publishing Ltd.
5th World Multidisciplinary Earth Sciences Symposium, WMESS 2019 -- 9 September 2019 through 13 September 2019 -- Prague -- 155452
Keywords: Batch reactors; Earth sciences; Hydrides; Hydrogen; Polyethylene terephthalates; Pyrolysis; Sodium Borohydride; Boron hydrides; Environmental influences; Hydrogen donor; Nitrogen gas pressure; Polyethylene terephthalates (PET); Pyrolysis experiments; Reaction temperature; Waste polyethylene terephthalates; Plastic bottles